2022
DOI: 10.3389/fneur.2022.941256
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery priorities and community rehabilitation service preferences of spinal cord injury individuals and caregivers of Chinese ethnicity and cultural background

Abstract: IntroductionSpinal cord injury (SCI) causes significant and permanent disability affecting motor, sensory and autonomic functions. We conducted a survey on the priorities of functional recovery and preferences for community rehabilitation services in a cohort of Chinese individuals with SCI as well as the primary caregivers. The study also investigated their views on advanced technology and research.MethodsAn online platform with a self-administered questionnaire was used to collect the opinions of clients tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…The PLEX Community Survey identified SCI health-related topics including aging with SCI, bladder and bowel function, pain and inflammation, spasticity, sexual health, and upper limb function as some of their top priorities. This list of top priorities is consistent with the literature, which has reported aging with SCI, upper extremity function, bladder and bowel function, sexual function, standing and walking, and chronic pain as the top priorities for PLEX [16][17][18][19][20][21][22].…”
Section: Comparing Experiences Of Persons With Lived Experience With ...supporting
confidence: 87%
See 1 more Smart Citation
“…The PLEX Community Survey identified SCI health-related topics including aging with SCI, bladder and bowel function, pain and inflammation, spasticity, sexual health, and upper limb function as some of their top priorities. This list of top priorities is consistent with the literature, which has reported aging with SCI, upper extremity function, bladder and bowel function, sexual function, standing and walking, and chronic pain as the top priorities for PLEX [16][17][18][19][20][21][22].…”
Section: Comparing Experiences Of Persons With Lived Experience With ...supporting
confidence: 87%
“…With the aging population, the topic of aging with SCI has become important and there is a need for evidence-based education in this area [16,17]. Other current key priorities for persons with SCI include upper extremity function, bladder and bowel function, sexual function, standing and walking, chronic pain, and stress management, as well as establishing a relationship with their clinician [18,19]. In providing this education, it has also been identified that there is a need to share experiences of what it is like to live with the secondary aspects of health beyond the physical, including peer support, mental health, and the social aspects essential to supporting individuals with SCI and their adjustment to life [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, in some African countries [11], [12], the situation of inaccessibility to rehabilitation care is considerable. Barriers to access include several factors such as geographical distance, lack of public transportation, financial costs associated with travel and care, as well as insufficient awareness and education about the importance of rehabilitation after a spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with higher lesions, regaining arm and hand function was mentioned as the most important, while recovery of walking and sexual function was the highest priority for paraplegics. In a recent study on functional recovery priorities, most of the respondents were interested in trying advanced technology that would bring a significant improvement in their QOL [ 90 ]. Additionally, a better understanding of emotional and cognitive control could be critical for the selection of adaptive and flexible behavior [ 91 ].…”
Section: Constructing An Integrative Behavioral Approach For a Better...mentioning
confidence: 99%